A Restoring Ability and Stability Analysis of Sailboats Across Different Points of Sail - Kang, Gyungju (Engineering, Technology & Applied Science Research, 2026)
This study analyzes the restoring ability and stability of wind-powered leisure boats under varying angles of attack and side forces. Using fluid analysis and mathematical modeling, thrust and side forces were evaluated to clarify restoring characteristics. Results show that the angle of attack strongly affects sail aerodynamics, altering lift, drag, and corresponding thrust and side forces. Thrust and side force distributions identify optimal sailing angles, while restoring force analysis highlights the sail’s dominant role in heeling moments over the hull. The angle of vanishing stability was 98°, confirming stable behavior even at large heel angles. The findings provide practical insights for improving the design and safety of wind-powered boats.